Formulation of Integrative Curriculum Structure Based on Tawheed at Ar-Rohmah Integral High School Malang - Asshahi, Arfafi; Amien, Saiful; Yusuf, Zulfikar (UMSU, 2025)
This article aims to determine the structure of the integrative curriculum based on monotheism implemented by SMA Integral Ar-Rohmah Malang. This study uses a qualitative approach with a case study type, because this study describes the curriculum structure from the foundation, objectives, vision, mission, strategy and curriculum content. Data collection was carried out using observation, interview and documentation techniques. For data analysis techniques with data condensation, data presentation and conclusions. Furthermore, data validity testing was carried out using triangulation techniques and sources to prove that the data received was valid. The results of the study showed that the curriculum used at SMA Integral Ar-Rohmah Malang is a combination of the national curriculum (Independence Curriculum), the Hidayatullah diniyah curriculum and the Hidayatullah fostering curriculum. This integrative curriculum based on monotheism is applied in every subject including intra and extra, in daily practice this curriculum applies the values of monotheism as the opening, content and closing of the teaching and learning process.